Do You Speak Dialect? Yes! - Vytautas Kardelis; Gabriela Forgeron (Lietuvių Kalba)
This article constitutes a continuation of the publication ‘Measuring Pronunciation: A Discursive Research Model’ (Kardelis, 2023).The primary objective of the paper was to apply the discourse model of dialectality measurement and to assess its implementation of the behavioural dimension of the trinomial model of language attitudes. The objective of the study was to empirically examine speakers’ attitudes towards the utilisation of dialectal language in informal settings with family members and friends from their native land. To this end, two tasks were identified: firstly, to present the course of the research and discuss the results, and secondly, to outline the research perspectives. The methodological principle of the study was the link between the cognitive and the emotional ↔ behavioural dimension. In essence, the methodology involved a dual-faceted approach: first, to ascertain whether informants employed dialectal language in informal settings with family members and friends from their country of origin; and second, to examine the practical implementation of this linguistic phenomenon.